The Model of Management of the Masela Block Based on People's Welfare in Maluku - Jarot Digdo Ismoyo (Administrative Law Departement Faculty of Law Universitas Sebelas Mare, 2020)
This research is motivated by the wealth of Indonesia, which has a fertile layer of land and there are very large deposits of minerals, oil and gas, this potential should ideally be managed for the welfare of the people. This research was aimed at explaining and analyzing the failure of mining management in Indonesia and the management model of the Masela Block based on the people's welfare in Maluku. This study uses normative legal research methods with data sources in the form of primary and secondary legal materials. The results showed that the discovery of the Masela Block gave the local government an opportunity to actively participate in mining management and that the oil and gas rich Masela Block to be exploited was a golden opportunity for the Maluku local government to actively participate in the oil and gas mining sector in an effort to improve people's welfare. Keywords: Mining; Masela Block; Maluku.